FORMULATION AND STABILITY TEST OF CREAM FROM JUICE OF BELIMBING WULUH (AVERRHOA BILIMBI l.) - Feronika Evma Rahayu; Annysa Ellycornia Silvyana; Lia Warti; Dentri Asih (Journal of Research in Pharmacy and Pharmaceutical Sciences, 2022)
Research on cream formulations using starfruit (Averrhoa bilimbi L.) juice has been carried out to determine the effect of sodium lauryl sulfate on the physical stability of cream from starfruit juice. Carambola wealth as an active substance is made in cream with varying concentrations of sodium lauryl sulfate of 1%, 1.5%, 2%, and 2.5%. The evaluation was carried out in the form of organoleptic tests, homogeneity, cream type, pH, viscosity, centrifugation, and freeze-thaw. Data analysis was carried out using statistical tests using ANOVA which has a 95% confidence level (α = 0.05), the test is continued with the Tukey HSD test, and the analysis results show significant differences in each formula. The research results concluded that the higher the concentration of sodium lauryl sulfate as an emulsifying agent, the physical stability of the viscosity of the cream from starfruit juice increased.